O mito do herói e sua função social: um estudo psicanalítico - ANA TERCIA ROSA ALVES (2025)
Psychoanalysis seeks to understand human beings and society and observes in Mythology several cultural symbols that represent the connection between the unconscious and the conscious. The union between Psychoanalysis and Mythology enables various reflections, as myths are important for individuals as well as society. Otto Rank was one of the first researchers to study comparative Mythology through the application of the psychoanalytic method, analyzing the stereotypes of hero legends and comparing dreams with classical myths. Rank observed in his studies that mythical narratives from different civilizations had many similarities and conveyed desires and manifestations of human history. Considering this context, the present research aims to investigate the social function of the hero myth through the method of applied Psychoanalysis, based on the theoretical concepts developed by Otto Rank. Given the vast number of mythological heroes, it was necessary to select a character to illustrate the figure of the mythical hero. For this research, the character Bellerophon was chosen, one of the most revered heroes of Greek Mythology, whose mythological symbols remain popular in contemporary imagination. This research is justified by the significant contribution of Rank's work to applied Psychoanalysis in Mythology studies, aiding psychoanalysts in better understanding cultures and societies. The hypothesis to be upheld is that the primary function of the hero myth is to represent society's desires and aspirations, illustrating manifestations of the unconscious.